Vigilantism, Current Racial Threat, and Death Sentences - Carmichael, Jason T. (2007)
Capital punishment is the most severe punishment, yet little is known about the social conditions that lead to death sentences. Racial threat explanations imply that this sanction will be imposed more often in jurisdictions with larger minority populations, but some scholars suggest that a tradition of vigilante violence leads to increased death sentences. This study tests the combined explanatory power of both accounts by assessing statistical interactions between past lynchings and the recent percentage of African Americans after political conditions and other plausible effects are held constant. Findings from count models based on different samples, data, and estimators suggest that racial threat and lynchings combine to produce increased death sentences, but the presence of liberal political values explains the absence of death sentences. These findings both confirm and refine the political version of conflict theory because they suggest that the effects of current racial threat and past vigilantism largely directed against newly freed slaves jointly contribute to current lethal but legal reactions to racial threat